Integrated study of the microfossils of the upper Aptian (Lower Cretaceous) of the Sobradinho and Serra do Mãozinha sections (Araripe Basin, northeastern Brazil): Biostratigraphic and paleoenvironmental inferences - Nascimento, Luiz Ricardo S.L.; Arai, Mitsuru [UNESP]; Lacerda, Josefa Nilmara Lopes; Tomé, Maria Emilia; Araripe, Rilda; Barreto, Alcina; Oliveira, David Holanda de; Pedrosa Lemos, Flávia; Prado, Ludmila A.C.; Ng, Christiano (Elsevier, 2023)
The present study reports the results of an integrated analysis of the microfossil assemblages from the Sobradinho and Serra do Mãozinha sections of the upper Aptian Romualdo Formation in the Araripe Basin, northeastern Brazil. The analysis of the distribution pattern of palynomorphs (terrestrial and marine), foraminifera, and ostracods revealed the presence of the palynomorph Sergipea variverrucata and the ostracod Damonella grandiensis, which supported the allocation of the principal portion of the sections to the Sergipea variverrucata Palynozone (P-270) and Ostracod Biozone O11, which are both indicators of the Aptian (= Alagoas local Stage). The frequent occurrence of both marine and continental palynomorphs, as well as calcareous microfossils, provide evidence of a coastal marine to restricted transitional environments, under a semi-arid to arid climate, with two well-defined marine incursions. The highlight of the data from the Serra do Mãozinha section is a new record of the Subtilisphaera Ecozone. In this section, the monospecific Subtilisphaera microflora represents the interval of weak marine influence. By contrast, the Sobradinho section is characterized by the occurrence of calcareous microfossils, foraminiferal linings, and a previously undocumented association of dinocysts, including 13 genera with four taxa being identified to species. Of these, Atopodinium cf. Iuvene, Apteodinium maculatum, Batiacasphaera sp., Circulodinium sp., Impagidinium sp., Gonyaulacysta sp., and Pervosphaeridium sp. Were recorded in the Araripe Basin for the first time.
Keywords: Foraminifera; Ostracods; Paleogeography; Palynomorphs; Romualdo formation